PUBLIC SPENDING AND ECONOMIC GROWTH PERFORMANCE: EVIDENCE FROM NIGERIA - Olonite, Oluyemi Ayodele; Gurowa, Sani U.; Ibrahim, Kamaluddeen Funsho Adisa; Ajewole, John Olorunleke (International Journal of Research -GRANTHAALAYAH, 2021)
This study analysed the relationship between public spending and economic growth in Nigeria. The study used the secondary data from CBN Statistical Bulletin from 2004 – 2018. The Real Gross Domestic Product formed the dependent variable and the independent variable of interest were the Capital Expenditure on Economic Services, and Expenditure of Transfers. The variables were validated by conducting the unit root test using the Augmented Dickey Fuller (ADF) and Phillips Perron Test (PP), and the correlation coefficient were determined using STATA and the Pearson Product Moment Correlation. A multiple regression model was employed for the study and was analysed using the Generalized Least Squares (GLSs) with the aid of Eviews 11 statistical program. The results of the study indicated that Capital Expenditure on Economic Services has a positive and significant impact on Economic Growth while Expenditure on Transfer has a negative and insignificant impact on Economic Growth. The study recommends that Capital Expenditure on Economic Services should be maintained and increased and Expenditure on Transfer should be made Zero, also, the government should develop the refineries to start mass production in order to null off the negative effect of transfers (subsidy payment on oil import and price equalization).